1967
DOI: 10.1080/00288233.1967.10423088
|View full text |Cite
|
Sign up to set email alerts
|

Serpentine and dunite as magnesium fertiliser

Abstract: The uptake of magnesium by plants from the use of the magnesium silicates serpentine and dunite was compared with that from dolomite and talc-magnesite, the latter two minerals being commonly used magnesium fertilisers in Nelson.Tobacco plants, white clover, and perennial ryegrass were grown in pots filled with sawdust. Plant nutrients were supplied in solution, except magnesium, which was applied at different rates of ground fertiliser. Field trials with tobacco and pasture are also described.When the four ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

1968
1968
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 3 publications
0
6
0
1
Order By: Relevance
“…Serpentinite has no significant effect on the yield of perennial grasses, but significantly increase the magnesium concentration in the grass dry matter, which reduces the risk of hypomagnesaemia in cattle. It has been found that serpentinite can substitute more soluble magnesium fertilizer (Chittenden et al, 1967;Haynly et al, 2005). The research carried out in Lithuania showed that granular serpentinite significantly increased the total, marketable seed and fodder potato tubers yields of one shrub .…”
Section: Serpentinite (Magnesium Hydrosilicate) (Mg6[si4o10]•[oh]8 Ormentioning
confidence: 99%
“…Serpentinite has no significant effect on the yield of perennial grasses, but significantly increase the magnesium concentration in the grass dry matter, which reduces the risk of hypomagnesaemia in cattle. It has been found that serpentinite can substitute more soluble magnesium fertilizer (Chittenden et al, 1967;Haynly et al, 2005). The research carried out in Lithuania showed that granular serpentinite significantly increased the total, marketable seed and fodder potato tubers yields of one shrub .…”
Section: Serpentinite (Magnesium Hydrosilicate) (Mg6[si4o10]•[oh]8 Ormentioning
confidence: 99%
“…10 Indeed, due to the basicity, serpentinite has been used as a Mg source and replacement of lime. 11 In addition, due to the thermal properties of serpentinite it is also used as flux agent to produce thermal-phosphate fertilizers. 12 Previous studies have shown that alkaline metals, such as Li + , Na + and K + can be intercalated in the serpentinite structure and upon thermal treatment form different Mg silicates such as Li 4 SiO 4 /MgO, 13 Therefore, the K 2 MgSiO 4 phase produced from the available and low-cost serpentinite can be a source of K or Mg in slower release rates compared with traditional soluble sources, which could be highly advantageous as potential fertilizers.…”
Section: Introductionmentioning
confidence: 99%
“…O serpentinito é uma rocha que possui aplicações em diversos seguimentos, é utilizada como rocha ornamental [1], fertilizante fonte de MgO na agricultura [2], fonte de MgO no processo siderúrgico [3] e agente anticlustering nas pelotas utilizadas no processo de produção de ferro metálico através de redução direta [4]. Nos dois últimos exemplos o serpentinito passa por processo térmico durante sua utilização e com isso tem sua estrutura cristalina redefinida Tecnol Realizou-se também análise termogravimétrica em atmosfera inerte (N 2 ), de acordo com os parâmetros abaixo:…”
Section: Introductionunclassified